Impact of biochar on plant growth and uptake of ciprofloxacin, triclocarban and triclosan from biosolids. Issue 11 (1st November 2020) - Bair, Daniel A.; Anderson, Carolyn G.; Chung, Young; Scow, Kate M.; Franco, Roberta Brancher; Parikh, Sanjai J.
Abstract: Application of municipal biosolids in agriculture present a concern with potential uptake and bioaccumulation of pharmaceutical compounds from biosolids into agronomic plants. We evaluated the efficacy of biochar as a soil amendment to minimize uptake of antimicrobial agents (ciprofloxacin, triclocarban, and triclosan) in lettuce ( Lactuca sativa ) and carrot ( Daucus carota ) plants. Biochar reduced the concentration of ciprofloxacin and triclocarban in lettuce leaves and resulted in a 67% reduction of triclosan in carrot roots. There was no substantial difference in pharmaceutical concentrations in carrot and lettuce plant matter at low (2.0 g kg −1 soil) and high (20.4 g kg −1 soil) rates of applied biochar. The co-amendment of biochar and biosolids increased soil pH and nutrient content which were positively correlated with an increase in lettuce shoot biomass. Our results demonstrate the potential efficacy of using walnut shell biochar as a sorbent for pharmaceutical contaminants in soil without negatively affecting plant growth.